Fulfillment of Voting Rights for Persons with Disabilities in General Elections in Indonesia - Habib Anwar; Moh Saleh (Faculty of Law, Merdeka University Surabaya, Indonesia, 2025)
Human rights are fundamental rights inherent in every individual because of their existence as human beings and are based on their dignity. Fulfillment of the right to vote for people with disabilities in general elections is a concrete form of respect for political rights that are universal, inalienable, and guaranteed in national and international law. This study aims to analyze the legal regulations related to the fulfillment of voting rights for people with disabilities in Indonesia and evaluate their compliance with human rights principles. The problems raised in this study include how these legal regulations are formulated in laws and regulations, and to what extent their implementation has fulfilled the principles of non-discrimination and equality. This study uses a normative legal method with a statutory and conceptual approach. The statutory approach is used to examine regulations such as Law Number 8 of 2016, Law Number 7 of 2017, and other implementing regulations, while the conceptual approach is used to explore the principles and legal doctrines related to political rights for people with disabilities. The research results are expected to provide concrete recommendations in formulating more inclusive and equitable policies, in order to support the realization of an election system that guarantees equal political rights for all citizens without discrimination.